The Positive Politeness Strategies Used in “English for Nusantara” Textbook - Rita Erlinda; Herick Afrinursalim; Fadhil Dinarta (Journal of English Language Teaching and Linguistics, 2023)
The integration of pragmatic competence and politeness is an essential focus in the development of English learning materials like textbooks. Using appropriate textbooks can help students develop communicative competence as the primary goal of English language teaching as a foreign language. This study discusses the positive politeness strategy in the textbook "English for Nusantara". The present study used a qualitative approach with a documentary analysis design. The data were collected by analyzing the dialogues contained in the textbook. The theory of positive politeness strategy, developed by Brown and Levinson (1987), was used to examine the data. The findings revealed that there are eight positive politeness strategies used in the dialogues of the English for Nusantara textbook, namely (1) exaggerating one’s interest in, approval of, and sympathy of the listener, (2) employing in-group markers of identity, (3) requesting agreement, (4) requesting & promising, (5) involving the speaker and the listener in action and (6) offering or asking for an explanation, (7) using inclusive “we” form, and (8) giving (or asking for) reasons. The most dominant positive politeness strategy was ‘exaggerating interest in, approval of or sympathy with the hearers.’ EFL learners’ pragmatic competence will be increased when pragmatic contents, like politeness, are integrated into the textbook as English learning materials used by teachers in the classroom.